위암 발생의 민감성과 RNase3 유전자 다형성과의 연관성 - 구자욱(Ja Wook Koo); 강동백(Dong Baek Kang); 박원철(Won Cheol Park); 이영환(Young Hwan Lee); 강인홍(In Hong Kang); 채수천(Soo Cheon Chae); 이정균(Jeong Kyun Lee) (Annals of surgical treatment and research, 2010)
Purpose: RNase3 is a secretory ribonuclease, which is found in the eosinophilic leukocyte and involved in the innate immune system. Its cytotoxic activity is effective against a wide range of pathogens. We performed a case-control study to examine the relationship between RNase3 polymorphisms and the susceptibility of gastric cancer in Korean people. Methods: Blood sampling of stomach cancer and healthy persons groups were performed, Taqman in g.-550A＞G, polymerase chain reaction-restriction fragment length polymorphism in g.371C＞G, and high-resolution melt in g.499C＞G were analyzed. The three single nucleotide polymorphisms g.-550A＞G, g.371C＞G, and g.499C＞G in RNase3 and their haplotypes were analyzed. Results: The genotype and allele frequencies of RNase3 g.-550A＞G and g.371C＞G were not significantly increased in susceptibility of gastric cancer than control group. But, RNase3 CC genotype was associated with a significantly increased susceptibility of gastric cancer than control group (P=0.002). Also, RNase3 CC genotype was more specifically associated with a significantly increased susceptibility of middle and lower gastric cancer than upper gastric cancer (P=0.002). In haplotype of RNase3 SNP g.-550A, g.371G, and g.499C, there was significantly susceptibility of gastric cancer (P=0.004), and more specific influence on middle and lower gastric cancer than upper gastric cancer (P=0.006 vs 0.054). Conclusion: RNase3 g.499C＞G polymorphism may influence gastric cancers, and have a more specific influence on middle and lower gastric cancer rather than upper gastric cancer. But RNase3 g.-550A＞G, g.371C＞G polymorphisms need careful interpretation and confirmation in more larger studies. Purpose: RNase3 is a secretory ribonuclease, which is found in the eosinophilic leukocyte and involved in the innate immune system. Its cytotoxic activity is effective against a wide range of pathogens. We performed a case-control study to examine the relationship between RNase3 polymorphisms and the susceptibility of gastric cancer in Korean people. Methods: Blood sampling of stomach cancer and healthy persons groups were performed, Taqman in g.-550A＞G, polymerase chain reaction-restriction fragment length polymorphism in g.371C＞G, and high-resolution melt in g.499C＞G were analyzed. The three single nucleotide polymorphisms g.-550A＞G, g.371C＞G, and g.499C＞G in RNase3 and their haplotypes were analyzed. Results: The genotype and allele frequencies of RNase3 g.-550A＞G and g.371C＞G were not significantly increased in susceptibility of gastric cancer than control group. But, RNase3 CC genotype was associated with a significantly increased susceptibility of gastric cancer than control group (P=0.002). Also, RNase3 CC genotype was more specifically associated with a significantly increased susceptibility of middle and lower gastric cancer than upper gastric cancer (P=0.002). In haplotype of RNase3 SNP g.-550A, g.371G, and g.499C, there was significantly susceptibility of gastric cancer (P=0.004), and more specific influence on middle and lower gastric cancer than upper gastric cancer (P=0.006 vs 0.054). Conclusion: RNase3 g.499C＞G polymorphism may influence gastric cancers, and have a more specific influence on middle and lower gastric cancer rather than upper gastric cancer. But RNase3 g.-550A＞G, g.371C＞G polymorphisms need careful interpretation and confirmation in more larger studies. KCI Citation Count: 0